Comparing Connective Tissue Grafts and Collagen Matrix in Modified Coronally Advanced Tunnel Technique for RT1 Gingival Recession: A Randomized Controlled Clinical Trial - Ahmed Elbana; Wafaa Saleh; Jilan Youssef (BMC Oral Health)
Abstract Background The effectiveness of the modified coronally advanced tunnel (MCAT) technique in treating isolated gingival recession Type 1 (RT1) has been evaluated in a few studies. Hence, this prospective randomized controlled clinical trial was directed to assess the MCAT technique with connective tissue graft (CTG) or collagen matrix (CM) in improving clinical outcomes for isolated gingival recession type 1 (RT1), mainly the attached gingiva width (AGW) as a primary outcome. Despite the clinical relevance of AGW, there is a gap in the literature with limited studies concerning it as a primary outcome. Methods Forty patients were chosen and randomly assigned into either the control group (MCAT and CTG) or the test group (MCAT and CM) for short-term assessment (6 months) of single (RT1) gingival recession treatment. The primary outcomes were attached gingiva width (AGW), recession depth (RD), recession width (RW), and mean root coverage% (MRC%). The secondary outcomes included gingival thickness (GT), keratinized tissue width (KTW), periodontal probing depth (PPD), clinical attachment level (CAL), plaque index (PI), gingival index (GI), pink esthetic score (PES), root coverage esthetic score (RES), and patient-reported outcome measures (PROMs). The chi-square (χ²) test, Mann-Whitney U test, t-test, and Friedman test were used for statistical analysis of the outcomes. Results Forty patients aged 18 to 45 years were enrolled in the current study. Evaluation of the primary outcomes (AGW, RD, RW) showed significant differences in the studied groups from the baseline to the final follow-up period (p-value ≤ 0.05). The MRC % results showed significant improvement after the 6-month follow-up period. For the control group, the MRC% was 97.08 ± 9.09, while for the test group, the MRC% was 96.75 ± 7.99. The PI, GI, PPD, CAL, KTW, PES, or RES values did not significantly differ among the two groups from the baseline to the final follow-up period. Conclusion Our study supported the efficacy of the MCAT in isolated gingival recession coverage. The CM may act as an alternative to CTG by increasing the patient’s satisfaction and reducing tissue morbidity and surgical time. Trial registration The current clinical trial was retrospectively registered in ClinicalTrials.gov (ID: NCT06065774) and released on 11/18/2024.